Study on Optimization of Irrigation and Drainage Systems in Jombatan Village - Muhammad Arif Hakim; Mohamad Nasirudin; Canggih Nailil Maghfiroh (AGARICUS: Advances Agriculture Science & Farming, 2022)
The development and management of irrigation infrastructure from a historical perspective is closely related to national food security. In infrastructure management, irrigation must meet the needs of farmers. Every plant needs sufficient water to increase agricultural productivity and farmer's welfare. Meeting water needs requires adequate irrigation and drainage channels in each area. One of them is Jombatan Village, which is a village located in Kesamben District, Jombang Regency. Optimising the performance of irrigation and drainage channels in Jombatan Village requires a concrete step. This irrigation and drainage literature review discuss optimising the performance of irrigation and drainage channels. All irrigation and drainage canal buildings have the same conditions; namely, the walls of the buildings are overgrown by plants and moss, some of the walls of the canal buildings are damaged due to the lack of strength of the building structure. The effectiveness of irrigation and drainage channels in Jombatan Village is still not optimal because infrastructure maintenance is still lacking, and community knowledge is still lacking.